recall that for any root say x - a, namely x - a = 0, thus x = a, for such a root of a polynomial, f(x), based on the remainder theorem f(a) = 0.
to put it in different lingo, since we know that we have two factors (x - 2 ) and (x+1), that simply means we have two roots of x = 2 and x = -1, well, using the remainder theorem that simply means f(2) = 0 and f(-1) = 0.
![image](https://img.qammunity.org/2019/formulas/mathematics/middle-school/30o4y29vtytvi21dzqveeguio9k7jccc2l.png)
![image](https://img.qammunity.org/2019/formulas/mathematics/middle-school/10ydyt332rq4qr0o01lgtrp17bmd56jyy6.png)
and you can graph that, you'll see the roots or x-intercepts of -1 and 2 there.